P121 Clinical Decision Support: A Valuable Tool For Many Reasons. (15th August 2013) - Van Vegchel, T; Kersten, S; Harmsen, M
Abstract : Background: Oncology is complex and time-consuming care. Because evidence changes frequently, implementation of knowledge is viable for putting evidence into daily practice and decreasing variation in treatment advice. Context: Clinical Decision Support (CDS) based on Clinical Practice Guidelines improves both individual care for cancer patients, including increase in safety, efficiency and transparency and supports guideline developers adjusting implementation strategies and improving updating. Description of Best Practice: We developed a prototype, which uses input based on disease (TNM, stadium) and patient characteristics (co-morbidity, e.g.). First, recommendations were formulated as computer interpretable recommendations using IF…THEN rules. Second, the application assembled all information and combined them with alerts, namely contraindications and side effects, finally leading to treatment advice. We found that CDS is a viable way of assisting doctors and patients. Treatment advice is better suited to both evidence based recommendations and specific patient characteristics. Insight into why a certain choice is made improves confidence in the suggested treatment and compliance. Also, more gaps in knowledge were found and trial participation was improved. Lessons for Guideline Developers/Users: CDS: Can provide insight into the use of guidelines. For example, when a recommendation isn't followed, possible efforts in implementation (recommendation is not/poorly implemented) or update (recommendation is outdated) are needed. Rewriting recommendations increased consistent language used in guidelines, which include easy reuse of data between professionals, hospitals and Cancer Registry Updating guidelines is expensive and time consuming. The doctors (and patients) ability to respond to existing recommendations supports faster, more efficient and cheaper modular updates.